2010
DOI: 10.1007/s11244-010-9546-0
|View full text |Cite
|
Sign up to set email alerts
|

Selective Hydrogenation of Benzonitrile by Alumina-Supported Ir–Pd Catalysts

Abstract: The kinetics of liquid-phase hydrogenation of benzonitrile have been examined alumina supported Ir, Pd and Ir-Pd catalysts. Benzonitrile disappearance TOF is 10-fold higher for Pd catalyst than it is for Ir catalyst. Benzylamine is produced preferentially over Pd, whereas dibenzylamine is produced principally over Ir. Non-monotonic activity and selectivity relationships with bimetallic composition are obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 13 publications
3
26
0
Order By: Relevance
“…Indeed, while the heating of Ir(acac) 3 /ASA in H 2 yields 1.5 ± 0.3 nm Ir particles, that of Pd(acac) 2 /ASA gives rise to 4.5 ± 1.3 nm Pd particles. This suggests a faster diffusion of Pd species on the support, as already proposed by López-De Jesús et al In regard to the similarities of our results with those for Ir-Pd/c-Al 2 O 3 synthesized from chlorinated precursors by these authors [32], the difference of interaction with the ASA surface, which is aluminarich [41]. In summary, appears to arise from the metal atoms themselves, that is, Ir interacts more strongly than Pd with the support.…”
Section: Metal-dependent Particle Size and Size-dependent Particle Cosupporting
confidence: 91%
See 3 more Smart Citations
“…Indeed, while the heating of Ir(acac) 3 /ASA in H 2 yields 1.5 ± 0.3 nm Ir particles, that of Pd(acac) 2 /ASA gives rise to 4.5 ± 1.3 nm Pd particles. This suggests a faster diffusion of Pd species on the support, as already proposed by López-De Jesús et al In regard to the similarities of our results with those for Ir-Pd/c-Al 2 O 3 synthesized from chlorinated precursors by these authors [32], the difference of interaction with the ASA surface, which is aluminarich [41]. In summary, appears to arise from the metal atoms themselves, that is, Ir interacts more strongly than Pd with the support.…”
Section: Metal-dependent Particle Size and Size-dependent Particle Cosupporting
confidence: 91%
“…Recently, López-De Jesús et al have synthesized Ir-Pd/c-Al 2 O 3 catalysts by impregnation of chlorinated precursors and calcinationreduction [32]. As in our case, the authors have observed an increase in the particle size with the Pd content.…”
Section: Metal-dependent Particle Size and Size-dependent Particle Cosupporting
confidence: 77%
See 2 more Smart Citations
“…Although the bulk immiscible iridium-palladium has been only scarcely studied till now (Tripathi 1991;Turchi 2006;Kolb 2006), a few experimental reports on this system show its actual interest for catalysis (López-De Jésus et al 2010;Shen et al 2010;Piccolo et al 2012). In particular, it has been shown that supported IrPd nanoalloys are more selective than their pure counterparts in the preferential oxidation of CO in hydrogen excess, a reaction used for the elimination of CO impurities in the H 2 production process (Morfin et al 2012;Zlotea et al 2014).…”
Section: Introductionmentioning
confidence: 99%